ANALISIS KEBUTUHAN PENGEMBANGAN E-MODUL FISINBERMA BERBANTUAN PHET UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR TINGKAT TINGGI SISWA SMA - Sujanem, Rai (Universitas Pendidikan Ganesha, 2025)
This research aimed at: 1) analysis of literature studies: essential concepts, characteristics of problem-based interactive physics (probinphys) e-modules assisted by PhET; 2) Field studies: essential concepts, facilities and infrastructure, references, learning methods, and obstacles in learning. The research subjects were class X students of SMAN Singaraja. The data collection method was by providing a checklist, making observations, and interviews. The results of the need analysis are: 1) Literature study products: (a) list of essential concepts of quantities, units, and measurements, (b) characteristics of the probinphys e-module: problem presentation, theoretical basis, example questions and exercises. 2) Field study products: (a) list of essential concepts; (b) laboratory equipment, ICT, internet access, and PhET simulations are available; (d) the methods applied by teachers are discussion, lecture, and PBL methods, not yet using probinphys teaching materials, (e) the obstacles are time problem, difficulty preparing ill-structure problems, and slow internet access. Keywords: probinphys e-module, hots